The Role of Teachers in Increasing Low-Grade Students' Interest in Reading - Khasanah, Aulia Fajar; Setyowati, Ririn (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Teachers are not only one of the key factors in developing students' interest in reading, but also must have the ability to adjust to the various characteristics of students to increase their enthusiasm for reading.  The aim of this study is to explain the role of teachers in stimulating students' interest in reading as well as identifying factors that may hinder their interest in reading. The research design is qualitative collaborated with descriptive approach. Based on the results of research that has been obtained from the results of interviews and observations show that students ' interest in reading is still low. One of the reasons is the lack of motivation of students to read books. Many ways can be done by teachers so that students ' interest in reading increases. The role of teachers in increasing students ' interest in reading is as a creator, inspirer, facilitator, motivator.